Some Aspects of the Problem of Training of Future Teachers of Mathematics to the Independent Work of Students in Colleges Organization - Koroliuk, Olena (Pedagogical Discourse, 2013)
The article substantiates the need for training of future teachers of mathematics to the organization of independent work of students in colleges. The meanings of «independent work of students in colleges», «independent work organization», «managing of independent work» are analyszed and clarified. The main stages of its organization are allocated. The contents and the objectives of the managing of independent work in learning mathematics at different stages in colleges are disclosed.